Type 2 Innate Lymphoid Cell in Cardiovascular Diseases: Complexities and Potentials - Haibei Sun; Weizhuo Liu; Zelin Yu; Bin He (Intensive Care Research)
Abstract Innate lymphoid cells (ILCs) are a class of lymphocytes that do not express specific antigen recognition receptors, which play a significant role in various diseases due to their unique immunomodulatory functions. Among these, type 2 innate lymphoid cells (ILC2s) form a distinct subpopulation and are recognized as key mediators in anti-infective and allergic responses. Cardiovascular diseases are a leading cause of intensive care unit admissions. Cardiovascular diseases, including myocardial infarction and heart failure, have a complex pathogenesis involving inflammation, tissue injury, and repair. Recent studies suggest that ILC2s are crucial in cardiovascular diseases by regulating inflammation, promoting tissue repair, and facilitating cardiac remodeling through the secretion of anti-inflammatory cytokines like IL-4, IL-5, and IL-13, etc. However, ILC2s have a complex role in cardiovascular health, potentially contributing to adverse cardiac remodeling and heart failure in certain contexts. Thus, the precise mechanisms by which ILC2s influence cardiovascular disease processes remain incompletely understood. This review summarizes recent advances in understanding ILC2 mechanisms in cardiovascular diseases and explores their potential as therapeutic targets, aiming to identify new treatment strategies.